PROMOTION AND EMPLOYEE PERFORMANCE IN THE NIGERIAN CIVIL SERVICE - Onyema, Chiemeka (African Journal of Social and Behavioural Sciences, 2025)
This work focused on the effect of promotion on employee performance in the Nigerian Civil Service. The study specifically investigated the effects of receiving a promotion and experiencing promotion stagnation on employee performance in the Federal Civil Service of Imo State, Nigeria. The target population consisted of 1086 federal civil servants in 32 organisations. However, a sample of 1007 federal civil servants emerged from a total population survey of the target population. The 32 organisations, comprising ministries, departments, and agencies, were selected because they are strictly subject to the Civil Service Rules. The research data represent the responses of the sample population to the research questionnaire, which had a reliability coefficient estimate of 0.742. The survey data were subjected to logistic regression analysis to investigate whether promotion predicts employee performance in federal civil service organisations. The research hypothesis was tested using the Pearson correlation coefficient to determine whether a relationship existed between promotion and employee performance. The results of the logistic regression analysis revealed that receipt of a promotion (p = .039) was statistically significant. This meant that the receipt of promotion likely had a significant effect on employee performance. The hypothesis test result revealed that there existed a statistically significant positive relationship between promotion and employee performance in the Federal Civil Service, Imo State (r = .167, p < .000). The analyses results suggested that promotion affected employee performance in the Federal Civil Service, Imo State.